A Research Director's Perspective of the Issue of the Neglect of Churches in Voluntary Action Research - Morris, Orrin D. (Review of religious research, 1983)
Three research issues are addressed in terms of needs: (1) greater emphasis on theoretical integrity of religious research, (2) increased interdisciplinary activity, and (3) better understanding of the nature of sacred and secular perceptions of social researchers. The author writes from the perspective of an action researcher in a national agency of a conservative protestant denomination.